2013
DOI: 10.1155/2013/239034
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Behavioral Symptoms following Antibiotic Therapy in a 14-Year-Old Male with Autism

Abstract: This case report describes the benefits of antibiotic and antifungal therapy on behavior in a child with autism undergoing treatment for encopresis. Over the course of treatment, the child exhibited a reduction in aberrant behaviors, increased gastrointestinal function, and improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Interestingly, a small clinical study of vancomycin treatment in ASD children reported some improvements in ASD behaviors, which waned when antibiotic treatment was discontinued (50), suggesting that the microbiome may contribute actively to the severity of behavioral abnormalities in ASD. Particular case studies also link antibiotic treatment to improvements in ASD behaviors and co-morbid conditions (51). In addition, the antibiotics d-cycloserine and minocycline are promising in light of their ability to treat behavioral symptoms of ASD in clinical trials and animal models (5254).…”
Section: Potential Roles For the Microbiome In Asdmentioning
confidence: 99%
“…Interestingly, a small clinical study of vancomycin treatment in ASD children reported some improvements in ASD behaviors, which waned when antibiotic treatment was discontinued (50), suggesting that the microbiome may contribute actively to the severity of behavioral abnormalities in ASD. Particular case studies also link antibiotic treatment to improvements in ASD behaviors and co-morbid conditions (51). In addition, the antibiotics d-cycloserine and minocycline are promising in light of their ability to treat behavioral symptoms of ASD in clinical trials and animal models (5254).…”
Section: Potential Roles For the Microbiome In Asdmentioning
confidence: 99%
“…In a randomized double-blind, placebo-controlled trial in children and adolescents with FXS, three months of minocycline treatment improved anxiety and mood-related behaviours 238 . Although antibiotic treatment may also improve symptoms in idiopathic forms of ASD 239241 , ASD with regressive features may be resistant to minocycline therapy 242 . The exact immunomodulatory mechanisms of minocycline are unknown; however, it may exert its effects through a combination of suppressing cytokine signalling, enhancing neurotrophic factor secretion and suppressing mTOR signalling 243 .…”
Section: Perspectivementioning
confidence: 99%
“…The exact immunomodulatory mechanisms of minocycline are unknown; however, it may exert its effects through a combination of suppressing cytokine signalling, enhancing neurotrophic factor secretion and suppressing mTOR signalling 243 . Minocycline could relieve ASD-related phenotypes directly through altering neural function or indirectly through ameliorating ongoing immune dysfunction or through regulating the intestinal microbiota 241 .…”
Section: Perspectivementioning
confidence: 99%
“…Similarly, for ASD, an improvement in symptoms has been observed after intervention. Here, antibiotic treatment alleviated anxiety in children with ASD [40], and treatment with vancomycin, an antibiotic used to treat infections with Clostridia, resulted in significant short-term improvement in neurobehavioral symptoms in children with autism [41]. Following the discontinuation of vancomycin, the behavioral improvements largely waned.…”
Section: Introductionmentioning
confidence: 99%